Microbial Community Succession and Response to Environmental Variables During Cow Manure and Corn Straw Composting - Meng, Qingxin; Yang, Wei; Men, Mengqi; Bello, Ayodeji; Xu, Xiuhong; Xu, Benshu; Deng, Liting; Jiang, Xin; Sheng, Siyuan; Wu, Xiaotong; Han, Yue; Zhu, Haifeng (Frontiers in Microbiology, 2019)
In composting system, the composition of microbial communities is determined by the constant change in the physicochemical parameters. This study explored the dynamics of bacterial and fungal communities during cow manure and corn straw composting using high throughput sequencing technology. The relationships between physicochemical parameters and microbial community composition and abundance were also evaluated. The sequencing results revealed the major phyla included Proteobacteria, Bacteroidetes, Firmicutes, Chloroflexi and Actinobacteria, Ascomycota and Basidiomycota. Linear discriminant analysis effect size (LEfSe) illustrated that Actinomycetales and Sordariomycetes were the indicators of bacteria and fungi in the maturation phase respectively. Mantel test showed that NO3−-N, NH4+-N, TN, C/N, temperature and moisture content significantly influenced bacterial community composition while only TN and moisture content had a significant effect on fungal community structure. Structural equation model (SEM) indicated that TN, NH4+-N, NO3−-N and pH had a significant effect on fungal abundance while TN and temperature significantly affected bacterial abundance. Our finding increases the understanding of microbial community succession in cow manure and corn straw composting under natural conditions.